2013
DOI: 10.1590/s0102-86502013000400012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of obstructive sleep apnea in obese patients scheduled for bariactric surgery

Abstract: PURPOSE:To evaluate the frequency of obstructive sleep apnea (OSA) in obese patients scheduled for bariatric surgery and their identification for risk of OSA by Berlin Questionnaire (BQ) and excessive daytime sleepiness by Epworth Sleepiness Scale (ESS). METHODS:Fifty nine patients were evaluated by BQ and ESS. Out of these individuals, 35 performed a full-night sleep study using a type 3 portable monitoring (PM). The questionnaire results were compared for gender and BMI. The presence and severity of OSA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…The cardio-respiratory consequences of OSA may exacerbate in the postoperative period due to the adverse effect of general anesthetics and pain treatment for breathing control and upper airways muscle tone. Based on such information, many authors have suggested that it is important to identify patients suffering from OSA [ 11 , 12 ]. Earlier studies of preoperative sleep disorders prior to bariatric surgery demonstrated an overall prevalence rate of OSA ranging from 48 to 91 % [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cardio-respiratory consequences of OSA may exacerbate in the postoperative period due to the adverse effect of general anesthetics and pain treatment for breathing control and upper airways muscle tone. Based on such information, many authors have suggested that it is important to identify patients suffering from OSA [ 11 , 12 ]. Earlier studies of preoperative sleep disorders prior to bariatric surgery demonstrated an overall prevalence rate of OSA ranging from 48 to 91 % [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, BMI may not accurately detect adiposity in patients under the age of 30 with BMIs of less than 30 kg/m 2 [25][26][27]. Neto et al employed the Epworth sleepiness scale (ESS) and the Berlin questionnaire (BQ) to assess the prevalence and risk of OSA in obese patients undergoing bariatric surgery [28]. The relationship between the severity of OSAS and obesity demonstrates joint causality.…”
Section: Discussionmentioning
confidence: 99%
“…Young et al (1993) 9 noted that regardless of severity, women did not report symptoms that differed significantly from those of men and snoring was still the most sensitive and strongest predictor of OSA. .Lopes Neto JM(2013) 10 found that the frequency of obstructive sleep apnea (OSA) in obese patients scheduled for bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%